The Development of a Comprehensive and Coherent Theory of Learning. (13th January 2015) - Illeris, Knud
<x xml:space="preserve">Abstract</x> This article is an account of how the author developed a comprehensive understanding of human learning over a period of almost 50 years. The learning theory includes the structure of learning, different types of learning, barriers of learning as well as how individual dispositions, age, the learning environment and general social and societal conditions influence learning possibilities. All this started when the author, aged 27, broke off his career as a travel agent and joined a course for matriculation at the university. He found this course extremely ineffective and got the idea that a firm knowledge about how human learning takes place might be a starting point for the development of more engaging and effective learning, teaching, schooling and education. Over the years, he gathered inspiration from a broad range of learning theorists such as Piaget, Rogers, Ausuble, Leithäuser, Schön, Kolb, Furth, Mezirow, Kegan and his own Danish instructor, Thomas Nissen. But the theory was built up as his own structure by critically adding new elements from the examination of other theories and carefully analysing experience from teaching, supervising and observing learning courses at all levels from primary school to adult education and university studies.